2022
DOI: 10.3390/ijerph192013395
|View full text |Cite|
|
Sign up to set email alerts
|

Post-Mortem Cardiac Magnetic Resonance in Explanted Heart of Patients with Sudden Death

Abstract: Background: We sought to evaluate the diagnostic accuracy of post-mortem cardiac magnetic resonance (PMCMR) of explanted hearts to detect the cardiac causes of sudden death. Methods: PMCMR was performed in formalin-fixed explanted hearts of 115 cases of sudden death. Histological sampling of myocardium was performed using two different approaches: (1) guideline-based sampling; (2) guideline-based plus PMCMR-driven sampling. Results: Forensic diagnosis of cardiac cause of death was ascertained in 72 (63%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Early sudden cardiac death may end a clinically silent course of disease or deteriorate a symptomatic clinical spectrum, such as AMI, arrhythmia, or heart failure [98]. Although sudden death mainly affects children and adolescents, it can also occur 10 to 20 years after diagnosis, making KD unsafe at any age [99].…”
Section: Discussionmentioning
confidence: 99%
“…Early sudden cardiac death may end a clinically silent course of disease or deteriorate a symptomatic clinical spectrum, such as AMI, arrhythmia, or heart failure [98]. Although sudden death mainly affects children and adolescents, it can also occur 10 to 20 years after diagnosis, making KD unsafe at any age [99].…”
Section: Discussionmentioning
confidence: 99%
“…With the addition of a PMCMR-driven strategy, the matching went up to 102 cases (89%) (sensitivity of 89%; AUC of 0.88). The authors found that PMCMR exhibited a high degree of accuracy in identifying the cardiac etiology of sudden death and might be used as a legitimate adjunct for forensic diagnosis [ 57 ]. In addition, in another study by Baronti et al, performed on five individuals with SCD who had previously received mRNA vaccinations, the PM-CMR revealed ischemic lesions and coronary artery stenosis in all cases [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in veterinary medicine, cardiac MRI can be challenging due to anesthesia-induced immobilization and variations in animal body size. Postmortem imaging has garnered attention in human forensic medicine for aiding the diagnosis of sudden death by visualizing cardiovascular abnormalities [ 1 , 3 , 13 ]. This report describes a postmortem MRI performed on the heart of a Noma horse foal that died suddenly.…”
mentioning
confidence: 99%
“…In this case, the morphological structure of the cardiac malformation could be understood in 3D by postmortem MRI. Postmortem imaging, particularly MRI, has emerged as a useful adjunct tool to autopsies in cardiac evaluation [ 1 , 3 , 13 , 17 , 19 ]. This technique has the potential to contribute significantly to veterinary medicine research and knowledge advancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation